MODERN APPROACH TO THE DEVELOPMENT OF PROFESSIONAL COMPETENCE OF FUTURE INDEPENDENTGOGS - Teshabayeva Oygul Fazliddinovna (Bright Mind Publishing, 2025)
Properly organized independent work creates the basis for students to acquire learning experience, life skills, social and professional attractiveness, opportunities for personal and self-esteem. Independent education forms professional competencies.
Keywords: Competence, independent learning, deaf teacher, students, teacher, specialization, differentiated approach.